Ketahanan Moderasi Beragama Mahasiswa di Tengah Melting Pot Gerakan Keagamaan di Surakarta - Moh Ashif Fuadi (Al-Adabiya: Jurnal Kebudayaan dan Keagamaan, 2021)
Besides being famous as a city that has a rich Javanese cultural heritage, in Surakarta, Central Java, there are also various religious-based views and organizations, ranging from those that can be categorized as the moderate groups to the radical ones. The existence of one of the PTKIN (State Islamic Universities), namely UIN Raden Mas Said in Surakarta, certainly makes it a place for various views to flow. This study discusses the influence of religious background on the religious attitudes of UIN Raden Mas Said students. Through qualitative research methods employing surveys, this study concludes that the large variety of religious organizations in Surakarta does not necessarily affect students' religious understandings and attitudes. In contrast to several previous studies which indicated a relationship between student activities and the puritan fundamentalist movement, this study proves that the students still have a moderate, inclusive, tolerant religious understanding, respect for tradition, and are loyal to the state ideology. Amid the potential for exclusivity as an excess of being in a melting pot of various religious views, students have resilience in maintaining an attitude of religious moderation. Selain populer sebagai kota yang memiliki kekayaan warisan budaya Jawa, di Surakarta Jawa Tengah juga terdapat beragam aliran dan organisasi masyarakat berbasis keagamaan, mulai dari yang dapat dikategorikan moderat hingga radikal. Keberadaan salah satu PTKIN (Perguruan Tinggi Keagamaan Islam Negeri), yakni UIN Raden Mas Said di Surakarta, tentu menjadikannya sebagai tempat bermuaranya berbagai aliran. Penelitian ini membahas pengaruh latar belakang keagamaan terhadap sikap beragama mahasiswa UIN Raden Mas Said. Dengan metode penelitian kualitatif melalui survei, penelitian ini menghasilkan kesimpulan bahwa banyaknya ragam aliran keagamaan yang di Surakarta tidak otomatis memengaruhi pemikiran mahasiswa menjadi radikal. Berbeda dengan beberapa penelitian sebelumnya yang mengindikasikan adanya hubungan antara kegiatan mahasiswa dengan gerakan puritan fundamentalis, penelitian ini membuktikan bahwa mahasiswa masih memiliki pemahaman keagamaan yang moderat, inklusif, toleran, menghargai tradisi, dan setia terhadap ideologi negara. Di tengah potensi eksklusifitas sebagai ekses dari keberadaannya di melting pot ragam aliran, mahasiswa memiliki ketahanan dalam menjaga sikap moderasi beragama.